2021
DOI: 10.1088/1674-1056/abeee7
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of reactive melt infiltration to fabricate Co-Si/C composites

Abstract: Cobalt-silicon based carbon composites (Co–Si/C) have established a noteworthy consideration in recent years as a replacement for conventional materials in the automotive and aerospace industries. To achieve the composite, a reactive melt infiltration process (RMI) is used, in which a melt impregnates a porous preform by capillary force. This method promises a high-volume fraction of reinforcement and can be steered in such a way to get the good “near-net” shaped components. A mathematical model is developed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…The precise biochemical mechanism for the effect of oxymetazoline hydrochloride ophthalmic solution (0.1%) on blepharospasm is still being researched, but some preliminary conclusions can be drawn. Because oxymetazoline hydrochloride ophthalmic solution (0.1%) stimulates contractions in Müller's muscle, and Müller's muscle is responsible for maintaining upper eyelid elevation, reductions in blepharospasm may have been due to the strengthening of Müller's muscle according to findings from an earlier study [5]. The results from another earlier study also suggested that the upper eyelids would remain elevated, preventing involuntary closure of the eyelids resulting from these spasms [7].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The precise biochemical mechanism for the effect of oxymetazoline hydrochloride ophthalmic solution (0.1%) on blepharospasm is still being researched, but some preliminary conclusions can be drawn. Because oxymetazoline hydrochloride ophthalmic solution (0.1%) stimulates contractions in Müller's muscle, and Müller's muscle is responsible for maintaining upper eyelid elevation, reductions in blepharospasm may have been due to the strengthening of Müller's muscle according to findings from an earlier study [5]. The results from another earlier study also suggested that the upper eyelids would remain elevated, preventing involuntary closure of the eyelids resulting from these spasms [7].…”
Section: Discussionmentioning
confidence: 93%
“…Abnormally low-lying upper eyelids is a condition known as blepharoptosis [5]. Blepharoptosis can be classified as acquired, neurogenic, myogenic, mechanical, aponeurotic, or traumatic [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations